Plant-growth promotion by proteobacterial strains depends on the availability of phosphorus and iron in Arabidopsis thaliana plants - Orellana, Daniela; Machuca, Daniel; Ibeas, Miguel Angel; Estevez, José Manuel; Poupin, María Josefina (Frontiers in Microbiology, 2022)
Phosphorus (as phosphate, Pi) and iron (Fe) are critical nutrients in plants that are often poorly available in the soil and can be microbially affected. This work aimed to evaluate how plant-rhizobacteria interaction changes due to different Pi or Fe nutritional scenarios and to study the underlying molecular mechanisms of the microbial modulation of these nutrients in plants. Thus, three proteobacteria (Paraburkholderia phytofirmans PsJN, Azospirillum brasilense Sp7, and Pseudomonas putida KT2440) were used to inoculate Arabidopsis seeds. Additionally, the seeds were exposed to a nutritional factor with the following levels for each nutrient: sufficient (control) or low concentrations of a highly soluble source or sufficient concentrations of a low solubility source. Then, the effects of the combinatorial factors were assessed in plant growth, nutrition, and genetic regulation. Interestingly, some bacterial effects in plants depended on the nutrient source (e.g., increased aerial zones induced by the strains), and others (e.g., decreased primary roots induced by Sp7 or KT2440) occurred regardless of the nutritional treatment. In the short-term, PsJN had detrimental effects on plant growth in the presence of the low-solubility Fe compound, but this was not observed in later stages of plant development. A thorough regulation of the phosphorus content was detected in plants independent of the nutritional treatment. Nevertheless, inoculation with KT2440 increased P content by 29% Pi-deficiency exposed plants. Conversely, the inoculation tended to decrease the Fe content in plants, suggesting a competition for this nutrient in the rhizosphere. The P-source also affected the effects of the PsJN strain in a double mutant of the phosphate starvation response (PSR). Furthermore, depending on the nutrient source, PsJN and Sp7 strains differentially regulated PSR and IAA- associated genes, indicating a role of these pathways in the observed differential phenotypical responses. In the case of iron, PsJN and SP7 regulated iron uptake-related genes regardless of the iron source, which may explain the lower Fe content in inoculated plants. Overall, the plant responses to these proteobacteria were not only influenced by the nutrient concentrations but also by their availabilities, the elapsed time of the interaction, and the specific identities of the beneficial bacteria.